Prince Svyatoslav Vsevolodovich of Chernigov, "Kinngmaker" in Suzdalia (1174-1179) - Dimnik Martin (Сіверщина в історії України, 2015)
Prince Svyatoslav Vsevolodovich of Chernigov (1164-1177) had Monomashichi blood in him since his mother Maria was Prince Vladimir Monomakh’s granddaughter. The genealogical bond between him and the Yur’evichi dynasty of Suzdalia therefore may have been a strong factor in influencing him to foster friendly relations with them. Svyatoslav gave four Yur’evichi sanctuary in Chernigov and after Prince Andrey Bogolyubskiy’s assassination in 1174 he helped Mikhalko and after him Vsevolod, as the most senior Yur’evich in the Monomashichi family in Suzdalia, to attain control of Suzdalia. By backing their claims to the throne of Vladimir on the Klyaz’ma Svyatoslav showed that he supported the ladder system of princely succession, the system that Yaroslav the Wise had advocated. Чернігівський князь Святослав Всеволодович (1164-1177 рр.) був споріднений з Мономашичами через свою мати Марію, онучку князя Володимира Мономаха. Його генеалогічний зв'язок з суздальською династією Юр'євичів міг сприяти розвитку дружніх відносин з ними. Святослав надав притулок чотирьом Юр'євичам у Чернігові. Після вбивства кн. Андрія Боголюбського 1174 р. він допоміг старшим в їх роді Михалку та пізніше Всеволоду здобути князівську владу на Суздальщині. Через підтримку цих претендентів на стіл Володимира-на-Клязьмі Святослав виявив себе прихильником родової системи престолонаслідування, що запровадив Ярослав Мудрий Черниговский князь Святослав Всеволодович (1164-1177 гг.) имел кровное родство с Мономашичами через свою мать Марию, внучку князя Владимира Мономаха. Его генеалогическая связь с суздальской династией Юрьевичей могла способствовать развитию дружеских отношений с ними. Святослав предоставил убежище четырем Юрьевичам в Чернигове. После убийства кн. Андрея Боголюбского в 1174 г. он помог старшим в их роде Михалку и затем Всеволоду вокняжиться в суздальской земле. Поддержав этих претендентов на стол во Владимире-на-Клязьме, Святослав проявил себя сторонником «лествичной» системы престолонаследования, установленной кн. Ярославом Мудрым.